Escisión y circularidad, o el doble sueño que confunde: “Las ruinas circulares” de Borges y la biblioteca de Alonso Quijano - González, Javier Roberto (2025)
The purpose of this work is to analyze the related figures of the protagonists of “The Circular Ruins” by Borges and Don Quixote by Cervantes based on three premises: 1) that in both narratives, the device known as metalepsis, or a level shift between diegesis and extradiegesis, is present as a key reading element; 2) that the motif of the dreamed dreamer is in both texts the symbol of a split or duplication of the self; 3) that this motif does not demonstrate the dreamlike or unreal nature of the world but, on the contrary, affirms the consistency and substance of dreams, which are sufficient in themselves to construct a real and invulnerable cosmos capable of producing both terror and relief.